PERAN KURSUS PRA NIKAH DALAM MEMPERSIAPKAN PASANGAN SUAMI-ISTRI MENUJU KELUARGA SAKINAH - Iskandar, Zakyyah (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Pre marriage course is a government effort to press the high rates of divorce, domestic violence and other family problems. The procedure for execution and materials to be delivered in pre marriage course has been set in the Regulation Director General of Islamic Guidance No. DJ.11 / 491 of 2009 about bride courses is then refined by the Regulation Director General of Islamic Guidance No. DJ.II / 542 of 2013 about Guidelines for Implementation of Pre Marriage Course. This article examines how the rules that have been set by the government assembled premarital courses in Indonesia and slightly described how the implementation of the pre marriage course in neighboring countries. Premarital course program recommendation is still not compulsory for couples who want to get married, therefore the implementation is still deemed less effective. But if the pre marriage course conducted seriously and as an obligation, it can be predicted that pre-marriage courses will serve healthful Indonesian families from the disease of violence, injustice in household and divorce and will created a harmonious family. [Kursus pra nikah merupakan upaya pemerintah dalam menekan tingginya angka perceraian, kekerasan dalam rumah tangga dan problem keluarga lainnya. Tata cara pelaksanaan dan materi yang akan disampaikan dalam kursus pra nikah telah diatur dalam Peraturan Dirjen Bimas Islam No. DJ.11/491 tahun 2009 tentang Kursus Calon Pengantin yang kemudian disempurnakan dengan Peraturan Dirjen Bimas Islam No. DJ.II/542 tahun 2013 tentang Pedoman Penyelenggaraan Kursus Pra Nikah. Artikel ini mengkaji bagaimana peraturan yang telah diatur oleh pemerintah terakit kursus pra nikah di Indonesia dan sedikit mendeskripsikan bagaimana pelaksanaan kursus pranikah di negara tetangga. Program kursus pra nikah masih bersifat anjuran bukan kewajiban bagi pasangan yang ingin menikah, oleh karena itu dalam pelaksanaannya masih dirasa kurang efektif. Namun jika kursus pra nikah dilaksanakan secara serius dan sebagai suatu kewajiban, maka dapat diprediksikan bahwa kursus pra nikah akan berfungsi menyehatkan keluarga Indonesia dari penyakit kekerasan, ketidakadilan dalam rumah tangga serta perceraian dengan terbinanya keluarga sakinah.]